Investigation on revenue recognition and debtors impairment: a case of TelOne (pvt) limited (2010-2014) - Muzite, Nyasha (Midlands State University, 2017)
This project investigates on revenue recognition and debtors impairment at TelOne (Pvt) Limited, the period under review being 2010 to 2014. The research aims to explore on how debtors impairment can be done .The determination of revenue recognition is also investigated upon in this research. This research project highlights briefly on the background of the study, as well as the approach taken by the researcher to address the research problem. The available literature on revenue recognition and debtors impairment was used in conducting the objectives of this research. Ways and means on how debtors can be impaired and when to impair debtors was stated by different authors. Research objectives on relationship between debtors impairment and revenue and how the credit risk of TelOne (Pvt) Limited clients can affect the impairment of debtors are also discussed. The research was done by using purposive sampling whilst gathering information by using questionnaires and interviews. Findings and responses from questionnaires and interviews conducted by the researcher on TelOne management and employees are presented and summarised in under the umbrella term Presentation and Analysis. These responses are linked to what is said on literature review. Conclusions on the research project and some recommendations on when to do debtors impairment and how revenue can be recognised correctly are stipulated in this research. This is to avoid overstating or understating of the values of debtors and revenue in the financial statements of TelOne. The contribution of this study to the existing literature is to show debtors impairment play a crucial role in the correct valuation of debtors. The underlying reason is that TelOne provide services and products to their clients being their debtors thus they should be valued correctly.